2015
DOI: 10.1097/ftd.0000000000000158
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Drug Monitoring of Levetiracetam and Lamotrigine

Abstract: These findings emphasize the need to monitor relatively newer anticonvulsants, lamotrigine and levetiracetam, especially among children and when other anticonvulsant comedications are prescribed or discontinued in the treatment regimen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 21 publications
2
19
0
Order By: Relevance
“…Similarly, the trend of a 30-40% higher clearance in children has been supported by Toublanc et al The authors have reported that the PK of LEV in children are similar to adults except that 30-40% higher doses are required in children to achieve similar drug exposure due to higher clearance (29). In general, children younger than 10 years of age have had the highest clearance, followed by those older than 11 and adults followed by elderly patients with the lowest level of clearance (6,28). On the other hand, a pharmacokinetic study conducted on 361 Chinese children aged 6 months to 14 years with epilepsy have found LEV clearance to be 50% lower than that of Caucasian children with a reported average elimination half-life of 8.13 hours (30) similar to the half-life associated with adults and clearance values of 0.96 ml/min/kg(1).…”
Section: Pediatricsmentioning
confidence: 98%
See 2 more Smart Citations
“…Similarly, the trend of a 30-40% higher clearance in children has been supported by Toublanc et al The authors have reported that the PK of LEV in children are similar to adults except that 30-40% higher doses are required in children to achieve similar drug exposure due to higher clearance (29). In general, children younger than 10 years of age have had the highest clearance, followed by those older than 11 and adults followed by elderly patients with the lowest level of clearance (6,28). On the other hand, a pharmacokinetic study conducted on 361 Chinese children aged 6 months to 14 years with epilepsy have found LEV clearance to be 50% lower than that of Caucasian children with a reported average elimination half-life of 8.13 hours (30) similar to the half-life associated with adults and clearance values of 0.96 ml/min/kg(1).…”
Section: Pediatricsmentioning
confidence: 98%
“…Consistent with other AEDs, there have not been any randomized controlled trials performed with LEV to determine whether TDM improves efficacy and tolerability compared to usual care. Furthermore, a robust correlation between efficacy and plasma concentrations of LEV has not been shown in either adults or children (4)(5)(6)(7)(8). Nevertheless, variable reference ranges have been suggested with the most commonly cited one being 12-46 mg/L (9).…”
Section: Therapeutic Drug Monitoringmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of these AEDs, such as LTG, LCM, ZNS, or felbamate, show significant interindividual pharmacokinetic variability due to interactions or metabolism polymorphisms, as they are substrates of hepatic cytochromes or glucuronosyltransferases. Other newer generation AEDs have less pharmacokinetic variability (LEV, TPM, OXC), but still show significant changes in their bioavailability with certain comedications or under specific physiological modifications, such as pregnancy . At times, those pharmacokinetic changes may exert dramatic consequences …”
mentioning
confidence: 99%
“…Other newer generation AEDs have less pharmacokinetic variability (LEV, TPM, OXC), but still show significant changes in their bioavailability with certain comedications or under specific physiological modifications, such as pregnancy. [23][24][25] At times, those pharmacokinetic changes may exert dramatic consequences. 26,27 TDM utility for newer generation AEDs was never assessed in a controlled trial.…”
mentioning
confidence: 99%